Tolerance and nutritional therapy of dietary fibre from konjac glucomannan hydrolysates for patients with inflammatory bowel disease (IBD) - Suwannaporn, P.; Thepwong, K.; Tester, R.; Al-ghazzewi, F.; Piggott, John Raymond [UNESP]; Shen, N.; Chen, Z.; Chen, F.; Yang, J.; Zhang, D.; Tang, M. (Elsevier, 2013)
Carbohydrates may provide an alternative therapeutic approach for a number of digestive health disorders such as inflammatory bowel disease (IBD). The aim of this work was to characterise the tolerance and efficacy of low and high molecular weight konjac glucomannan hydrolysates within healthy volunteers and patients suffering from IBD and associated gut conditions. These conditions included constipation, Crohn's disease and ulcerative colitis. For general tolerance, fourteen patients participated whilst for the digestive disorder trial, there were twenty. Scores of taste/texture of the product, bowel movement, stool consistency, diarrhoea, existence/absence of blood in the faeces, abdominal pains, flatulence, vomiting, fever, improvement of life style after use, willingness to use in the future and clinician's statements about each patient's conditions before and after use were recorded. The results showed that the hydrolysates were tolerated well for patients with diarrhoea and had a significant improvement on bowel movement, stool consistency, abdominal pain and flatulence after ten days. With respect to effects on IBD, there was a significant health benefit after fourteen days of consumption for bowel movement, stool consistency, diarrhoea, existence/absence of blood in the faeces, abdominal pain, flatulence and vomiting. Most patients declared an improvement of their life style after consuming the hydrolysates. The use of konjac glucomannan hydrolysates as a therapeutic agent or adjunct to standard treatments could prove a successful tool for the treatment of a range of disorders; although large scale studies are required to characterise further the role of the carbohydrates.
Keywords: Konjac glucomannan hydrolysates; Inflammatory bowel disease (IBD); Dietary fibre; Nutritional therapy